Expert System Design for Early Detection of Tuberculosis Disease (Case Study at Demak District Health Office) - Dewi, Adinda Cipta; Adi, Kusworo; Martini, Martini (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to design an expert system for early detection of Tuberculosis (TB) disease. The existence of this system is reduce the number of TB patients in the community. The expert system concept developed is building relationships of TB symptoms based on knowledge obtained from the TB programmer at the Demak District Health Office and the form used for TB screening as a reference for knowledge in this system. Based on the results, the system is designed to be able to diagnose TB disease based on the symptoms felt by the user. It will validate rule matches based on 1 main symptom and 6 additional symptoms to get TB diagnosis results, called suspected tuberculosis or not suspected tuberculosis.